Solve for y 11y-3-6y=6y-1

Math
11y-3-6y=6y-1
Subtract 6y from 11y.
5y-3=6y-1
Move all terms containing y to the left side of the equation.
Tap for more steps…
Subtract 6y from both sides of the equation.
5y-3-6y=-1
Subtract 6y from 5y.
-y-3=-1
-y-3=-1
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Add 3 to both sides of the equation.
-y=-1+3
Add -1 and 3.
-y=2
-y=2
Multiply each term in -y=2 by -1
Tap for more steps…
Multiply each term in -y=2 by -1.
(-y)⋅-1=2⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=2⋅-1
Multiply y by 1.
y=2⋅-1
y=2⋅-1
Multiply 2 by -1.
y=-2
y=-2
Solve for y 11y-3-6y=6y-1

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top